Mutations in 3β‐hydroxysteroid‐δ8, δ7‐isomerase paradoxically benefit epidermal permeability barrier homeostasis in mice. Issue 3 (30th November 2020) - Dang, Erle; Man, George; Lee, Dale; Crumrine, Debbie A.; Mauro, Theodora M.; Elias, Peter M.; Man, Mao‐Qiang
Abstract: Inherited or acquired blockade of distal steps in the cholesterol synthetic pathway results in ichthyosis, due to reduced cholesterol production and/or the accumulation of toxic metabolic precursors, while inhibition of epidermal cholesterol synthesis compromises epidermal permeability barrier homeostasis. We showed here that 3β‐hydroxysteroid‐δ8, δ7‐isomerase‐deficient mice (TD), an analog for CHILD syndrome in humans, exhibited not only lower basal transepidermal water loss rates, but also accelerated permeability barrier recovery despite the lower expression levels of mRNA for epidermal differentiation marker‐related proteins and lipid synthetic enzymes. Moreover, TD mice displayed low skin surface pH, paralleled by increased expression levels of mRNA for sodium/hydrogen exchanger 1 (NHE1) and increased antimicrobial peptide expression, compared with wild‐type (WT) mice, which may compensate for the decreased differentiation and lipid synthesis. Additionally, in comparison with WT controls, TD mice showed a significant reduction in ear thickness following challenges with either phorbol ester or oxazolone. However, TD mice exhibited growth retardation. Together, these results demonstrate that 3β‐hydroxysteroid‐δ8, δ7‐isomerase deficiency does not compromise epidermal permeability barrier in mice, suggesting that alterations in epidermal function depend on which step of the cholesterol synthetic pathway is interrupted. But whether these findings in mice could be mirrored in humans remains to be determined.